Compute functional analysis leveraging the IAAS private cloud computing service model in packstack development - Mohamad Iqbal Suriansyah; Iyan Mulyana; Junaidy Budi Sanger; Sandi Winata (Teknik Informatika Fakultas Ilmu Komputer Univeristas Muslim Indonesia, 2021)
Analyzing compute functions by utilizing the IAAS model for private cloud computing services in packstack development is one of the large-scale data storage solutions. Problems that often occur when implementing various applications are the increased need for server resources, the monitoring process, performance efficiency, time constraints in building servers and upgrading hardware. These problems have an impact on long server downtime. The development of private cloud computing technology could become a solution to the problem. This research employed Openstack and Packstack by applying one server controller node and two servers compute nodes. Server administration with IAAS and self-service approaches made scalability testing simpler and time-efficient. The resizing of the virtual server (instance) that has been carried out in a running condition shows that the measurement of the overhead value in private cloud computing is more optimal with a downtime of 16 seconds.